2019
DOI: 10.1259/bjro.20180026
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of the gantry sag effect in clinical SRS plans

Abstract: Objectives: The gantry sag introduces a largely reproducible variation of the radiation field center around the radiation isocenter. The purpose of this work is to assess the change of the dose distribution caused by the gantry sag in clinical stereotactic plans. Methods: Brain stereotactic radio surgery treatment plans were evaluated and grouped according to radiation therapy planning technique. Group 1 was planned with volumetric arc therapy technique using coplanar arcs while Group 2—non-coplanar arcs. To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…and McCallum‐Hee et al. reported that the effect of gantry sag is conspicuous in rotational irradiation using small fields 28,29 . Gantry sag could be the reason for the variation in coplanar and non‐coplanar beams using the 0.5 × 0.5 cm 2 field in this study.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…and McCallum‐Hee et al. reported that the effect of gantry sag is conspicuous in rotational irradiation using small fields 28,29 . Gantry sag could be the reason for the variation in coplanar and non‐coplanar beams using the 0.5 × 0.5 cm 2 field in this study.…”
Section: Discussionsupporting
confidence: 46%
“…This effect is considered to be caused by reported that the effect of gantry sag is conspicuous in rotational irradiation using small fields. 28,29 Gantry sag could be the reason for the variation in coplanar and non-coplanar beams using the 0.5 × 0.5 cm 2 field in this study. In addition, owing to the variety of detectors in this study, there was a detector-specific uncertainty.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Despite all efforts to improve patient positioning and delivery accuracy, mechanical imperfections of these machines remain. [3][4][5][6][7][8] With the increasing consideration of irradiation of multiple metastases as a treatment option, 9 and the increasing use of singleisocenter multi-target irradiations, 10 geometric problems come even more into the focus.…”
Section: Introductionmentioning
confidence: 99%
“…While dedicated machines for high precision and accuracy irradiations exist, these recommendations can typically also be met with conventional linear accelerators (Linacs). Despite all efforts to improve patient positioning and delivery accuracy, mechanical imperfections of these machines remain 3–8 . With the increasing consideration of irradiation of multiple metastases as a treatment option, 9 and the increasing use of single‐isocenter multi‐target irradiations, 10 geometric problems come even more into the focus.…”
Section: Introductionmentioning
confidence: 99%